Fluorogenic Selective and Differential Medium for Isolation of Enterobacter sakazakii - Oh, Se-Wook (American Society for Microbiology, 2004)
4-Methylumbelliferyl-α-d-glucoside, the fluorogenic substrate of α-glucosidase, was used as a selective marker to develop a differential medium for Enterobacter sakazakii. This bacterium showed strong fluorogenic characteristics clearly distinguishable from other microorganisms. On the basis of reducing background noise, an optimum basal medium and nitrogen source were selected. Incubation conditions were optimized.